2002
DOI: 10.1046/j.0014-2956.2001.02723.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel silkworm (Bombyx mori) phenol UDP‐glucosyltransferase

Abstract: Sugar conjugation is a major pathway for the inactivation and excretion of both endogenous and exogenous compounds. We report here the molecular cloning and functional characterization of a phenol UDP-glucosyltransferase (UGT) from the silkworm, Bombyx mori, which was named BmUGT1. The complete cDNA clone is 1.6 kb, and the gene is expressed in several tissues of fifth-instar larvae, including fat body, midgut, integument, testis, silk gland and haemocytes. The predicted protein comprises 520 amino acids and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 48 publications
2
50
0
Order By: Relevance
“…We demonstrated that antibiotics used clinically to treat infected humans are effective in silkworms, and that the ED 50 values of the antibiotics used in the silkworm infection model are consistent with those obtained in mammalian animal models (Hamamoto et al, 2004(Hamamoto et al, , 2005Hamamoto & Sekimizu, 2005;Kaito et al, 2002Kaito et al, , 2005. Silkworms have enzymes, P450s and conjugating enzymes (Hamamoto et al, 2005;Li et al, 2005;Luque et al, 2002) that are involved in metabolizing antibiotics. Silkworms are large enough for antiviral agents to be injected into their midgut and haemolymph by using syringes.…”
Section: Introductionsupporting
confidence: 60%
“…We demonstrated that antibiotics used clinically to treat infected humans are effective in silkworms, and that the ED 50 values of the antibiotics used in the silkworm infection model are consistent with those obtained in mammalian animal models (Hamamoto et al, 2004(Hamamoto et al, , 2005Hamamoto & Sekimizu, 2005;Kaito et al, 2002Kaito et al, , 2005. Silkworms have enzymes, P450s and conjugating enzymes (Hamamoto et al, 2005;Li et al, 2005;Luque et al, 2002) that are involved in metabolizing antibiotics. Silkworms are large enough for antiviral agents to be injected into their midgut and haemolymph by using syringes.…”
Section: Introductionsupporting
confidence: 60%
“…1) In fact, most of the compounds studied as substrates for insect glucosyltransferases have been plant and synthetic phenolics. [26][27][28] In Drosophila melanogaster, variations in the UDP-glucosyltransferase activity have been analyzed by using the xenobiotic compounds, 1-naphtol and 2-naphtol. 29) In this study, however, we showed that M. separata larvae were able to transform such Bxs such as DIMBOA, HMBOA and MBOA to O-glucosides and methoxy glucoside carbamate as detoxification products.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, also UDP-glucuronosyltransferase (UGTs) isozymes, which are important phase II enzymes for detoxification of B[a]P metabolites, exhibit a broad pH range from 5.5 to 8.5 in which they can function (Basu et al 2004). The UGTs superfamily is large, and therefore, UGT’s are active over a very wide pH range, and each UGT has its own optimal pH (Luque et al 2002). Since B[a]P metabolizing enzymes have different relative activities at different pH, it can be expected that B[a]P metabolism is significantly affected by pH.…”
Section: Discussionmentioning
confidence: 99%